Inaccurate Interpretation Of Offshore Geotechnical Site Investigation Results And Risk Associated - A Case Study Of Conductors Collapse In Driving - Hodjat] [Shiri (Deep Foundations Institute, 2006)
A 4-legged jacket structure was installed by an Offshore Installation Contractor (OIC) in the Persian Gulf. In addition to four open-end pipe piles, six conductors were installed by OIC. During the installation of the piles and conductors, some cemented layers were encountered, which had not been accounted for in the foundation design performed by an independent well known offshore geotechnical site investigation contractor (OGSIC). Six months later, the Drilling Company (DC) hired by Client to execute the wells, reported that all of the six conductors were presenting anomalies, such as vertical misalignments up to 10o and/or collapse of the conductors tip and mid height. The DC faced with serious problem in drilling of the wells and in spite of several times milling the conductors and spending 40 days unpredicted extra time, some of the routes could not be opened and Client lost millions of dollars due to direct and indirect associated costs and expenses. This paper presents a complete overview of all engineering, construction and specially geotechnical investigations and shows that how an inaccuracy in interpretations of the results of an offshore geotechnical site investigation as the main reason in this case study can cause serious damages to whole project with unbelievable time and cost impacts some times up to millions of dollars.